2016
DOI: 10.1111/jphp.12617
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of rocuronium in young adult and elderly patients undergoing elective surgery

Abstract: Elderly patients showed increased AUC/D and reduced total Cl compared to young adult patients due to the age-related reduced renal function. Differences in the PK-PD properties of rocuronium in elderly population are due to changes in drug disposition rather than to alterations in the sensitivity to the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Rocuronium has an onset time of approximately 135 s, and a clinical duration of action of approximately 81 min in the elderly (>80 years) after administration of 0.6 mg kg 5 . Rocuronium is primarily metabolized in the liver (70% passes unmetabolized via the bile) and excreted via the kidneys 6 . Elderly patients are at higher risk of residual neuromuscular blockade 7,8 which is associated with muscle weakness, double or blurred vision, impaired pulmonary function and a higher risk of postoperative respiratory complications in the post anaesthesia care unit 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Rocuronium has an onset time of approximately 135 s, and a clinical duration of action of approximately 81 min in the elderly (>80 years) after administration of 0.6 mg kg 5 . Rocuronium is primarily metabolized in the liver (70% passes unmetabolized via the bile) and excreted via the kidneys 6 . Elderly patients are at higher risk of residual neuromuscular blockade 7,8 which is associated with muscle weakness, double or blurred vision, impaired pulmonary function and a higher risk of postoperative respiratory complications in the post anaesthesia care unit 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Some research indicates that age is a factor that may influence the duration of action of muscle relaxants and that age-related reductions in cardiac output, renal and hepatic function, muscle mass, and the ability to regulate temperature are present in most elderly patients. [3,10]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that rocuronium leads to significantly longer muscle relaxation in elderly patients than in young adults. [3,10] The incidence of postoperative residual neuromuscular blockade has been reported to be approximately twice as high in elderly patients when compared to younger patients. [3] While repeated administration of cisatracurium during surgery does not lead to prolonged the duration and variability of duration of action.…”
Section: Introductionmentioning
confidence: 99%
“…From the pharmacokinetics standpoint, it is expected that recurarization occurs when low dose of sugammadex is administered to patients with deep muscle paralysis as demonstrated in previous studies. [20][21][22][23][24][25] Other studies demonstrated that the elderly patients respond differently to rocuronium 26,27 and sugammadex 28,29 in comparison with nonelderly patients, suggesting age-related differences in the pharmacodynamics and pharmacokinetics of rocuronium and sugammadex. We considered that potential pharmacodynamics/pharmacokinetics differences may be assessible by the change of the train-of-four ratio (primary outcome variable) between age groups.…”
Section: Editor's Perspective What We Already Know About This Topicmentioning
confidence: 99%